City and Religion: the catholic territoriality in Cult of Mercy at Teresina-PI (Research, Society and Development, 2021)
Religions play a prominent role in the cultural formation of society, influencing the way of human relating to space. Thus, studying the urban space considering the perspective of the Sacred enables a particular understanding of the city. The present work is an excerpt from the author's dissertation, developed at the Master in Geography at the Federal University of Piauí in 2018, whose investigative scope fell on the analysis of forms of territorialization of religion in the city of Teresina-PI. For the article, the Cult of Mercy was adopted as a cutout, a weekly Catholic event with strong popular appeal. It is noteworthy that, despite this celebration taking place in the circumscription of the Catholic Church, its territoriality and its ethos assume peculiarities in relation to the regular territory of the parish. In this sense, the objective is to understand the sacred territoriality built around the Cult of Mercy. Epistemologically anchored in the field of Geography of Religion, the research, of a qualitative nature, adopted ethnography as a method, based on the Geertz (2015) model aimed at the dense description of the phenomenon. To interpret the data, we sought to be anchored in content analysis (Bardin, 1977).